Implementation of e-SEKOCI (The Online Class of Sekolah Komplementer Cinta Ibu) in counselling midwives and pregnant women during COVID-19 pandemic - Rizka Ayu Setyani; Sumardiyono Sumardiyono (Journal of Community Empowerment for Health, 2021)
Pregnancy classes are vital for successful communication, information, and health education in maternity services. However, their implementation should be postponed during the COVID-19 pandemic to prevent COVID-19 transmission in pregnant women who are classified as a vulnerable group, especially if they had a history of pregnancy with non-communicable diseases. Therefore, we implemented e-SEKOCI (The Online Class of Sekolah Komplementer Cinta Ibu) which aimed to provide counselling and mentoring of pregnant women using social media WhatsApp group, Zoom Cloud meeting, Instagram, or YouTube. The implementation of e-SEKOCI began in March 2020 with 150 pregnant women in Indonesia. We also worked with teaching volunteers consisting of midwives and midwifery lecturers. In e-SEKOCI classes, expectant mothers were taught complementary midwifery care, such as mom and baby massage, prenatal and postnatal yoga, and self-hypnosis. Besides, pregnant women could also conduct online consultations with midwives about their pregnancies. Most of the participants said they were satisfied with e-SEKOCI, which included 80% in the health education program and 94% in the pregnancy consultation program. As many as 70% of participants prefer the WhatsApp group as a means of implementing e-SEKOCI. In conclusion, e-SEKOCI was effective as a media of midwife counselling for pregnant women, especially during the COVID-19 pandemic. The use of WhatsApp group media was recommended because it was easier to use and cost-effective.